The Effect of Climate Change on Environmental-Based Diseases in Palu City in 2015-2020 - Sanjaya, Kiki; Pitriani, Pitriani; Trisnowati, Putri; Handayani, Febi Dwi; Rau, Muh. Jusman; Hermiyanty, Hermiyanty (Journal of Health and Nutrition Research, 2022)
The purpose of this study was to determine the effect of climate change (temperature, humidity, wind speed, rainfall, and rainy days) on environmental-based diseases (DHF and ARI) in Palu City in 2015-2020. This study uses a quantitative method with an ecological study design. The sampling technique used total sampling where the samples were all cases of DHF and ARI from the Palu City Health Office and climate data from the Mutiara Palu Meteorological Station from 2015-2020. Data analysis using multiple linear regression test. The results of the study for the incidence of DHF showed, partially temperature (0.384 > 0.05), wind speed (0.873 > 0.05), rainfall (0.868 > 0.05). 0.05) and rainy days (0.608 > 0.05) had no effect on the incidence of DHF because the significance value was greater than 0.05. Simultaneously the test results obtained are (0.628 > 0.05), meaning that there is no significant effect between climate change and the incidence of DHF in Palu City because the F test results show a significance value greater than 0.05. The incidence of ARI shows that part there is a significant effect of temperature and humidity on the incidence of ARI with the same significant value (0.00 < 0.05) and positive (+) pattern, and there is a significant effect of wind speed and rainfall on the incidence of ARI with the same significant value (0.00 < 0.05) but with a negative pattern. The conclusion is that there is a significant effect of climate change on the incidence of ARI.